Mobilizing private finance for local infrastructure in Europe and Central Asia : an alternative public private partnership framework - Noël, Michel, 1954- (World Bank working paper, 2005)
"This paper presents an alternative framework for public-private partnerships (PPPs) that could revive the interest of various PPP stakeholders (central governments, local governments, private operators, and investors) in private participation in local infrastructure in Europe and Central Asia (ECA) and in other emerging markets. The study identifies the key impediments to private participation in infrastructure. It reviews recent trends in private participation in infrastructure (PPI) globally and in the ECA Region and assesses experiences by private investors of PPI in selected ECA countries. It also reviews investors' attitudes toward future PPI in ECA, drawing on key findings of existing surveys and on anecdotal evidence from interviews with private equity investors."--Jacket